SYNTHESIS, COMPLETE ASSIGNMENT OF 1H- AND 13C-NMR SPECTRA AND ANTIOXIDANT ACTIVITY OF NEW AZINE DERIVATIVE BEARING COUMARIN MOIETY - Ristić, Milenko; Dekić, Biljana; Radulović, Niko; Aksić, Marija (Bulletin of Natural Sciences Research, 2021)
In this research, the synthesis of a new azine derivative with coumarin moiety was performed in three reaction steps, starting from 4-hydroxycoumarin. The first step in synthesis was the acetylation of 4-hydroxycoumarin to yield 3-acetyl-4-hydroxycoumarin and then the obtained 3-acetyl-4-hydroxycoumarin was reacted with hydrazine hydrate and give a corresponding hydrazone. Condensation of the hydrazone with 4-ethoxy-3-methoxybenzaldehyde afforded the target compound 1-[1-(4-hydroxy-2-oxo-2H-chromen-3-yl)-ethylidene]-2-(4-etoxy-3-methoxybenzylidene)-hydrazine in a good yield. The resulting azine derivative is fully spectrally characterized, including complete assignment of 1H- and 13C-NMR spectra, as well as 2D NMR (1H-1H COSY, NOESY, HSQC and HMBC) spectra. The antioxidant activity of corresponding hydrazone and target compound was evaluated by DPPH method where hydrazone derivative displayed a significant and target azine good antioxidant activity, with IC50 (μM) values 11.69 and 216.60, respectively.
Keywords: Synthesis; Azines; Coumarins; Spectral analysis; 1H- and 13C-NMR; Antioxidant activity